Modelling, simulation and predictive control of a spark ignition engine. (29th August 2008) - Lorini, Gabriele; Miotti, Alessandro; Scattolini, Riccardo
Present-day spark ignition engines for the automotive industry are equipped with a number of actuators, such as the Electronic Throttle (ET), the Exhaust Gas Recirculation (EGR) and the Variable Valve Timing (VVT), which must be properly used to guarantee driveability and reduce fuel consumption and pollutant emissions. However, the underlying control problem is particularly difficult due to the strong interactions between these control variables and the main engine performance variables. In the first part of this paper, a control-oriented mean value model of a gasoline engine is presented and validated with real data. This model is then used in the synthesis of two control schemes with predictive capabilities. The first one is composed by a traditional static controller derived through a suitable optimisation problem and by an innovative dynamic term designed with Model Predictive Control (MPC). In the second scheme, the MPC controller is directly plugged into the loop for control of the torque request. Simulation results are reported to illustrate and compare the potentialities of the proposed approaches.